Evaluation of awareness, attitudes, and satisfaction levels of families of children with unilateral complete cleft lip and palate treated with nasal alveolar molding appliances - Hoang, Minh Phuong; Nguyen, Dinh Tien; Van, Thi Nhung; Ngo, Nam Hung; Chau, Ngoc Phuong Thanh; Hoang, Vu Minh; Tran, Tan Tai (Tạp chí Y Dược Huế, 2026)
Background: Cleft lip and palate (CLP) significantly impacts aesthetics, function, and the psychological well-being of both the child and their family. Presurgical orthopedics, particularly the Nasoalveolar Molding (NAM) appliance, it reduces the width of the lip cleft, improves nasal symmetry, and enhances feeding function for the child. This study aims to evaluate the awareness, attitudes, and satisfaction levels of families of children with unilateral complete CLP treated with NAM appliances, providing insight into the psychosocial benefits of this therapy. Materials and methods: A descriptive cross-sectional study was conducted on 31 parents or caregivers of children diagnosed with unilateral complete CLP. Participants were recruited from Hue University of Medicine and Pharmacy Hospital and Nghe An Obstetrics and Pediatrics Hospital between February 2022 and September 2024. Data on demographics, awareness, attitudes, and satisfaction were collected using a structured questionnaire administered through direct interviews after the completion of NAM therapy. Results: Among the 31 infants, none were able to breastfeed at birth. After the first day of NAM appliance placement, 30 infants (96.8%) were able to bottle-feed successfully. All parents believed that NAM improved their child’s appearance and considered the orthodontist a key member of the CLP care team. Majority (96.8%) recognized that NAM improved feeding. However, 67.7% of families reported that their quality of life was affected by having a child with CLP. Regarding attitudes, 77.4% of families felt the infant experienced discomfort during the impression-taking process, yet 96.8% found the treatment useful for the child and 19.4% found frequent follow–up appointments to be time–consuming or inconvenient. Nonetheless, all were willing to encourage other parents to use NAM before surgery. The overall satisfaction rate was high, with 74.2% of families reporting being “completely satisfied” with the treatment results. Conclusion: These findings underscore the importance of incorporating NAM into CLP care protocols and providing comprehensive support to families throughout the treatment process.